Laser for Colorectal Polyps and Cancer - R Lambert (Canadian Journal of Gastroenterology)
Laser photodestruction of colorectal polyps and cancer applies almost exclusively to neoplastic lesions. The best results are obtained in exophytic, noninfiltrative, noncircumferential tumours. Neodymium YAG (Nd:YAG) laser is the usual source, and sessions may be repeated at intervals of three to four days during tumour reduction, and at intervals of four to 12 weeks during maintenance therapy. Hemorrhage is a frequent but not severe complication; perforation is the potentially more severe complication. With experience, laser treatment complications decrease to less than 1%. The most common indication of laser phorodestruction concerns destruction of colorectal adenomas. Most indications in malignant adenomas are restricted to the rectum.